Hyperactive Rac converts sublethal to lethal trogocytosis in vivo - Lauren Penfield; Abhinava K. Mishra; Morgan Smith; Denise J. Montell (Proceedings of the National Academy of Sciences, 2026)
The small GTPase Rac is an essential regulator of cell shape, migration, macropinocytosis, and phagocytosis. We found that expression of constitutively active Rac G12V is sufficient to cause a few migratory cells called border cells to cannibalize neighboring nurse cells in the Drosophila ovary. Building on that insight, we engineered mammalian Rac-enhanced chimeric-antigen-receptor macrophages (RaceCAR-Ms) to avidly engulf and kill cancer cells. Here, we investigate the cellular and molecular mechanisms by which border cells efficiently kill the much larger nurse cells. Surprisingly, wild type border cells normally nibble on nurse cells as they migrate between them, and Rac G12V causes border cells to take larger, lethal bites. These larger bites trigger rapid germline shrinkage, nuclear damage, and caspase activation, which spreads through the nurse cell syncytium. Then, many somatic follicle cells join in to engulf the dying germline. Rac and the engulfment receptor Draper are critical for both sublethal and lethal nibbling (trogocytosis). Using clonal analysis, we show small groups of follicle cells expressing Rac G12V induced caspase activation in neighboring follicle cells while larger Rac G12V clones were required to cause germline killing. Increasing Draper expression or JNK activity in border cells also caused germline death, in a Rac-independent manner, suggesting that border cells can be activated to kill through multiple mechanisms. The series of events elucidated here reveals how hyperactivated Rac expressed in a few cells can trigger destruction of a much larger mass.